Gene expression and protein profiling of AGS gastric epithelial cells upon infection with Helicobacterpylori - Backert, Steffen; Gressmann, Helga; Kwok, Terry; Zimny-Arndt, Ursula; König, Wolfgang; Jungblut, Peter R.; Meyer, Thomas F. (Proteomics, 2005)
Helicobacter pylon, one of the most common bacterial pathogens, colonizes the human stomach and causes a variety of gastric diseases. This pathogen elicits a range of phenotypic responses in infected cultured AGS gastric epithelial cells, including expression of proinflammatory genes and changes in the actin cytoskeleton. Some of these responses are mediated by the type IV secretion system (T4SS) encoded by the cag pathogenicity island. We have used two global approaches, namely 2-DE combined with PMF and cDNA expression array analyses, to study in both a comprehensive and quantitative manner the protein profile and the temporal patterns of mRNA accumulation in AGS cells upon infection with H. pylori and isogenic T4SS mutants. We identified 140 transcripts and detected 190 protein species that were differentially regulated upon infection. Infection with wild-type H. pylori induced expression of a variety of host genes and changes in protein pattern involved in transcriptional responses, cell shape regulation and signal transduction. Among them, some were differentially regulated in a cag PAI-dependent manner, as shown by both the proteomic and cDNA expression array approaches. While 2-DE and PMF allowed us to examine the protein profiles in the infected host, array analysis enabled us to demonstrate dynamic temporal changes in host gene expression profile. In conclusion, our combined application of the two global approaches provides further molecular details on how the host cell responds to infection by H. pylon and its isogenic T4SS mutants on both transcriptional and protein levels. The findings pinpoint host proteins such as serine/threonine and tyrosine kinases, transcription factors, cell cycle related components and actin cytoskeletal signaling molecules as potential targets of individual H. pylori virulence determinants. This study serves as a basis for future work on transcription and proteome analyses of the H. pylori infection model. © 2005 Wiley-VCH Verlag GmbH & Co. KGaA.
Created from Fastlane, Scopus look-up
Keywords: cDNA expression array; Mass spectrometry; Molecular pathogenesis; Pathogenicity island; Type IV secretion